PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP MANAJEMEN LABA DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2022–2024) - Defti Agita Nursiti Sakinah; Abdul Rohman (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of Corporate Social Responsibility (CSR) on earnings management and the role of audit quality as a moderating variable in this relationship. The background of this study is based on the phenomenon that earnings management practices remain a serious concern in the accounting world, where company managers have the potential to manipulate financial information for personal or corporate gain. On the other hand, CSR, as a form of corporate social responsibility, is believed to reflect management's ethical commitment, which should mitigate such opportunistic behavior.The population in this study was all manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2022 and 2024. The sample was selected using a purposive sampling method based on certain predetermined criteria. The data used were secondary data obtained from annual reports and company financial statements published on the official IDX website. Earnings management was measured using discretionary accruals using the Modified Jones model, CSR was measured using a measurement index based on the Global Reporting Initiative (GRI), while audit quality was proxied by the size of Big Four and Non-Big Four Public Accounting Firms (KAP). The analytical method used was multiple linear regression with a Moderated Regression Analysis (MRA) test.The results provide empirical evidence that CSR negatively impacts earnings management, and that audit quality is unable to strengthen the relationship between CSR and earnings management. This research is expected to contribute to the development of accounting science, particularly in the field of corporate governance, and serve as a reference for investors, regulators, and other stakeholders in assessing the quality of corporate financial reporting.